Assessing the economic impact of a low-cost water-saving irrigation technology in Indian Punjab: the tensiometer. Issue 2 (17th February 2018) - Vatta, Kamal; Sidhu, R. S.; Lall, Upmanu; Birthal, P. S.; Taneja, Garima; Kaur, Baljinder; Devineni, Naresh; MacAlister, Charlotte
ABSTRACT: This article assesses the impact of the tensiometer on the consumption of groundwater and electric power in paddy cultivation in Indian Punjab, and its subsequent economic benefits. We find that compared to the continuous flooding method, the tensiometer-based application of irrigation reduces water and power consumption by 13%, cutting variable costs by 7% without any yield penalty. If 30% of the paddy area is irrigated following tensiometer-based schedules, then the state could save a total of 0.67 million ha m of water and 1516 million kWh of electric power in 2010–2025, with aggregate economic benefits of US$ 459 million.